2016
DOI: 10.1007/s13595-016-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Within-stem maps of wood density and water content for characterization of species: a case study on three hardwood and two softwood species

Abstract: Abstract• Key message Variability and interrelations between wood density, water content, and related properties were analyzed by CT scanning of five species. Relative water content of lumens is proposed as the best complement to basic specific gravity for discrimination of species with respect to their functioning. Handling Editor: Jean-Michel LebanContribution of the co-authors Fleur Longuetaud designed the experiment, run the data analysis and was the main writer. Frédéric Mothe designed the experiment, run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
2
35
0
3
Order By: Relevance
“…Indeed, this shows some resemblance to Kibblewhite's [79] schematic for mature corewood as a zone of wood with properties from pith to bark that differed from the juvenile corewood and juvenile outerwood found lower in the tree. Note that similar wood density maps have been generated for other conifer genera (Abies, Picea, Pseudotsuga), and while they show some longitudinal variability, they do not have the same general pattern of decreasing corewood density from the base to the top of the tree [80,81].…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, this shows some resemblance to Kibblewhite's [79] schematic for mature corewood as a zone of wood with properties from pith to bark that differed from the juvenile corewood and juvenile outerwood found lower in the tree. Note that similar wood density maps have been generated for other conifer genera (Abies, Picea, Pseudotsuga), and while they show some longitudinal variability, they do not have the same general pattern of decreasing corewood density from the base to the top of the tree [80,81].…”
Section: Discussionmentioning
confidence: 71%
“…The biological material was already used in a previous paper by Longuetaud et al (2016) which focused on the description of a method for mapping wood properties within-stems by using X-ray computed tomography. Five temperate species growing in France were sampled: three hardwoods (Quercus petraea/robur, Fagus sylvatica and Acer pseudoplatanus) and two softwoods (A. alba and P. menziesii).…”
Section: Experimental Materialsmentioning
confidence: 99%
“…By means of a more intensive sampling along the stem and by using X-ray computed tomography for analysing the sample discs, it is possible to access relatively easily radial, azimuthal and vertical variations within stem of some wood properties related to wood specific gravity and/or water content (Longuetaud et al 2016). (Longuetaud et al 2016) showed that among the studied variables, two were statistically independent and thus were suitable to be used as complementary traits for characterising species: basic specific gravity (BSG), which is the ratio of oven-dry weight to green volume relative to the density of water, and relative water content of lumens (RWC L ), which is the proportion of the cell voids occupied by water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations